The Role of Healthy Food to Improve the Physical and Spiritual Health of Students - Kasingku, Juwinner Dedy (JUPE : Jurnal Pendidikan Mandala, 2023)
This research delves into the influence of nutritious food on the health and spirituality of students. In an era of competitive education, attention to the physical and mental health aspects of students has become highly important. Nutritious food is acknowledged to have a positive impact not only on physical health but also on spiritual development. Nourishing and balanced meals can provide benefits for both physical and spiritual well-being. The fact that there is a lack of understanding about balanced nutrition triggers the necessity of this research. A qualitative method with a literature review approach is employed in this study. The research draws the conclusion that nutritious food significantly affects the wellbeing of students, encompassing both physical health and spirituality. Ultimately, this influence can support academic achievement and spiritual growth among students. The implications of this research underscore the pivotal role of wholesome nutrition in fostering holistic student welfare, emphasizing the need for educational programs that consider not only academic aspects but also the students’ physical and mental well-being.